1983
DOI: 10.7863/jum.1983.2.11.509
|View full text |Cite
|
Sign up to set email alerts
|

Sonomammographic manifestations of mammographically detectable breast microcalcifications.

Abstract: The sonographic appearances of ten breast carcinomas associated with microcalcifications were reviewed. None of the clusters of microcalcifications were visualized sonographically. All of the tumors were seen on sonomammography as either solid mass lesions or areas of acoustical shadowing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…This limited study supported the results of previous studies that showed that lower-frequency sonographic examinations may identify soft tissue breast masses but do not show calcifications well. 2,9 Furthermore, when we used the 7.5-MHz transducer, we found that the asso-…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…This limited study supported the results of previous studies that showed that lower-frequency sonographic examinations may identify soft tissue breast masses but do not show calcifications well. 2,9 Furthermore, when we used the 7.5-MHz transducer, we found that the asso-…”
Section: Resultsmentioning
confidence: 93%
“…In the past, several research studies have shown that sonography is insensitive for identifying microcalcifications. 1,2,[10][11][12] However, since these studies have been performed, there have been important improvements in sonographic equipment. Most major manufacturers now offer sonographic equipment with frequencies of 10 MHz or higher.…”
Section: A Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The general clinical experience is that current ultrasound technology and protocol do not reliably detect MCs [2]- [4]. This represents one of the fundamental limitations of current ultrasound technology in the imaging of the breast.…”
Section: Introductionmentioning
confidence: 98%